Thrombosis with Thrombocytopenia Syndrome (TTS) following AstraZeneca ChAdOx1 nCoV-19 (AZD1222) COVID-19 vaccination – A risk–benefit analysis for people < 60 years in Australia. Issue 34 (9th August 2021) - MacIntyre, Chandini Raina; Veness, Benjamin; Berger, David; Hamad, Nada; Bari, Noor
Abstract: The AstraZeneca ChAdOx1 nCoV-19 (AZD1222) vaccine is associated with Thrombosis with Thrombocytopenia Syndrome (TTS) in 3/100, 000 vaccinations with high fatality rates reported in many countries. We conducted a risk–benefit analysis for Australians aged 18–59 years, comparing the risk of vaccination versus infection, and rate of TTS to other vaccines which prompted policy change following rare adverse events – rotavirus, smallpox and oral polio vaccines. COVID-19 deaths over 12 months range from 0 to 417 in current and future worst case scenarios. In the past 15 months 20 COVID-19 deaths occurred in people < 60 years compared to 890 deaths over 60 years. The estimated possible number of TTS cases is 347, with vaccine-related deaths ranging from 17 to 153 if 80% of adults 18–59 years are vaccinated. The reported rate of TTS is in the same range as rare but serious adverse events associated with other vaccines that have been subject to policy change. In Australia, the potential risks of the AZD1222 vaccine in younger adults, who are at low risk of dying from COVID-19, may outweigh the benefits.